STRATEGI PENGEMBANGAN KOMUNITAS GURU SENI DAN SENIMAN PASURUAN (KGSP) MELALUI ANALISIS SWOT - Zenmira, Kharisma Nanda (Gapenas Publisher, 2023)
Komunitas Guru Seni dan Seniman Pasuruan (KGSP) is a community that serves as a forum for its members with art as the main element. KGSP has various concepts and goals in the field of art that require them to continue to develop in the community, so there is a need for strategic management as a form of effective development plan. To be able to carry out development, SWOT analysis can be used as an analysis in determining internal and external factors. The method used in this research is a qualitative method with a case study approach. Data collection techniques were carried out by interviews, observations and surveys. The results of the SWOT analysis show that the strategies that can be used by KGSP are generic expansion strategies and variations of strategies, namely concentric diversification, market penetration, product development and backward integration